CO2 emissions in the Amazon: are bottom-up estimates from land use and cover datasets consistent with top-down estimates based on atmospheric measurements? - Tejada, Graciela; Gatti, Luciana V.; Basso, Luana S.; Cassol, Henrique L. G.; Silva-Junior, Celso H. L.; Mataveli, Guilherme; Marani, Luciano; Arai, Egidio; Gloor, Manuel; Miller, John B.; Cunha, Camilla L.; Domingues, Lucas G.; et al. (Frontiers in Forests and Global Change, 2023)
Amazon forests are the largest forests in the tropics and play a fundamental role for regional and global ecosystem service provision. However, they are under threat primarily from deforestation. Amazonia's carbon balance trends reflect the condition of its forests. There are different approaches to estimate large-scale carbon balances, including top-down (e.g., CO2 atmospheric measurements combined with atmospheric transport information) and bottom-up (e.g., land use and cover change (LUCC) data based on remote sensing) methods. It is important to understand their similarities and differences. The purpose of this paper is to provide bottom-up LUCC estimates and to determine to what extent they are consistent with recent top-down flux estimates during 2010 to 2018 for the Brazilian Amazon. We combined LUCC datasets resulting in an annual LUCC map from 2010 to 2018 with emissions and removals for each LUCC and compared the resulting CO2 estimates with top-down atmospheric measurements. In the bottom-up total CO2 emissions (2010 to 2018), deforestation and degradation are the largest contributing classes with 58% (4,283 TgCO2) and 37% (2,740 TgCO2) respectively. Looking at the total carbon uptake, primary forests play a fundamental role with 79% (-5,901 TgCO2) and secondary forest growth with 17% (-1,243 TgCO2). Overall bottom-up net estimates are a carbon sink until 2014 and a source of emissions from 2015 to 2018. Comparing the net CO2 top-down and bottom-up flux, we see that top-down estimates are considerably higher. The difference between both approaches in 2010 is 1,121 TgCO2yr-1, in 2012 1,588 TgCO2yr-1. 2015 and 2016 have larger differences with 1,274 TgCO2yr-1 and 1,062 TgCO2yr-1 respectively. In 2017 and 2018 the differences are small with 296 TgCO2yr-1 and 157 TgCO2yr-1 respectively. The year with highest carbon emissions in both approaches is 2016. Bottom-up and top-down approaches have differences, the top-down considers all atmospheric fluxes, not only those related to LUCC; while in the bottom-up approach the CO2 estimates will vary according to the LUCC dataset. The annual scale of the bottom-up data restricts the seasonality and climatic influence analyzed by the top-down approach. Both approaches are essential for understanding the carbon cycle under climate change.